Assignment of Subject Headings and Classification Codes to e-books in South American University Libraries - Gil-Leiva, Isidoro; e Cruz, Maria Carolina Andrade [UNESP]; Redigolo, Franciele Marques [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (Editorial CSIC, 2024)
The integration of e-books into university libraries has allowed for interesting analysis and discussions in recent years about user preferences between printed and electronic books, the difficulties and challenges librarians face in their incorporation into libraries, among other aspects. However, with this work, the main objective is to analyze the changes that are occurring in South American university libraries regarding the processes of subject heading assignment and classification codes with the massive incorporation of e-books, as well as to understand librarians’ perceptions of these changes. To achieve this, we developed and distributed a web-based questionnaire consisting of twenty-four questions to a total of 1,175 university libraries in Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Peru, and Uruguay, from which we received 123 responses (10.5%). Among other findings, it is concluded that indexing and classification processes are losing relevance in librarians’ activities, the quality of metadata provided by publishers does not seem to be a significant factor for librarians, and furthermore, the data obtained does not clearly indicate a paradigm shift in relation to indexing and classification processes.
Asignación de encabezamientos de materias y códigos de clasificación a los e-books en bibliotecas universitarias de América del Sur
Keywords: Argentina; Bolivia; Brazil; Chile; classification; Colombia; e-books; Ecuador; Paraguay; Peru; South America; subject headings; university libraries; Uruguay